Association of Systemic Immune-Inflammatory Index with Risk of Foot Ulcer Amputation in Patients with Type 2 Diabetes Mellitus: Insights from a Cross-Sectional Study - Huang Z; Zheng X; Liang H; Zhong SY; Meng J; Yao J (Journal of Inflammation Research)
Zhongjie Huang,1,2,* Xifan Zheng,1,* Hao Liang,3 Song Yang Zhong,4 Jinzhi Meng,1 Jun Yao1 1Bone and Joint Surgery, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 2Bone and Joint Surgery, The Sixth Affiliated Hospital of Guangxi Medical University (The First People’s Hospital of Yulin), Yulin, Guangxi, People’s Republic of China; 3Guangxi University of Chinese Medicine, Nanning, Guangxi, People’s Republic of China; 4Guangxi Medical University, Nanning, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Yao, Bone and Joint Surgery, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China, Tel +86-771-5319091, Fax +86-771-5350031, Email yaojun800524@126.comObjective: Diabetic foot ulcer (DFU) is one of the complications of diabetes, which can lead to amputation and death. The systemic immune-inflammatory index (SII), calculated based on platelet, neutrophil, and lymphocyte counts, serves as a cost-effective and practical biomarker. This study aimed to explore the relationship between SII and amputation risk in patients with DFU.Methods: In this cross-sectional study, all eligible patients were divided into an amputation group and a non-amputation group based on their amputation status. Laboratory test data obtained on the first day of hospitalization were collected for all patients. SII was calculated from complete blood count parameters. Subgroup analysis, univariate analysis, and multivariate logistic regression were employed to assess the association between SII and amputation in patients with DFUs. Receiver operating characteristic (ROC) curves were used to evaluate the predictive accuracy of SII for amputation risk.Results: The amputation group exhibited significantly higher SII levels compared to the non-amputation group (p < 0.05). Multivariate logistic regression analysis, after adjusting for all covariates, revealed that SII remained independently associated with DFU-related amputation (OR = 1.019; 95% CI: 1.007– 1.031; p = 0.002). Subgroup analyses and interaction tests demonstrated that this positive association was not modified by age, sex, hypertension, smoking, or alcohol consumption (p for interaction > 0.05). In the ROC curve analysis, SII achieved an area under the curve (AUC) of 0.786 with a sensitivity of 77.70%. Reclassification based on propensity score matching showed that SII was significantly higher in the high-risk group than in the low-risk group(p < 0. 05).Conclusion: Higher SII levels in patients with type 2 DFU raise the risk of amputation. For assessing the risk of amputation in patients with DFUs, SII is likely to be a valuable biomarker for DFU amputation.Keywords: systemic immune-inflammatory index, diabetic foot ulcer, amputation, biomarker, cross-sectional study